2020
DOI: 10.1038/s42003-019-0741-7
|View full text |Cite|
|
Sign up to set email alerts
|

Cancer LncRNA Census reveals evidence for deep functional conservation of long noncoding RNAs in tumorigenesis

Abstract: Long non-coding RNAs (lncRNAs) are a growing focus of cancer genomics studies, creating the need for a resource of lncRNAs with validated cancer roles. Furthermore, it remains debated whether mutated lncRNAs can drive tumorigenesis, and whether such functions could be conserved during evolution. Here, as part of the ICGC/TCGA Pan-Cancer Analysis of Whole Genomes (PCAWG) Consortium, we introduce the Cancer LncRNA Census (CLC), a compilation of 122 GENCODE lncRNAs with causal roles in cancer phenotypes. In contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
141
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(147 citation statements)
references
References 74 publications
6
141
0
Order By: Relevance
“…We began with conventional manual curation of lncRNAs from the scientific literature, covering the period from January 2017 (directly after the end of the first CLC (42)) to the end of December 2018. We continued to use stringent criteria for defining cancer lncRNAs: genes must be annotated in GENCODE (here version 28), and cancer function must be demonstrated either by functional in vitro or in vivo experiments, or germline or somatic mutational evidence (see Methods) (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We began with conventional manual curation of lncRNAs from the scientific literature, covering the period from January 2017 (directly after the end of the first CLC (42)) to the end of December 2018. We continued to use stringent criteria for defining cancer lncRNAs: genes must be annotated in GENCODE (here version 28), and cancer function must be demonstrated either by functional in vitro or in vivo experiments, or germline or somatic mutational evidence (see Methods) (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that some literature-curated lncRNAs were also targeted by previously-overlooked mutations in published transposon insertion mutagenesis (TIM) screens (42). We hypothesised that this insight could be extended to identify novel functional cancer lncRNAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their epigenetic activity, TEs are active genetically and can alter transcript splicing patterns by becoming exonised into transcripts (Macfarlan et al 2012;Wang et al 2014;Goke et al 2015;Grow et al 2015). TEs make a major contribution to the sequences of long-non-coding RNAs (lncRNAs) (Lev-Maor et al 2008;Kelley and Rinn 2012;Kapusta et al 2013;Naville et al 2016), and whilst lncRNAs have roles in normal biological processes (Goff and Rinn 2015;Bourque et al 2018;Lu et al 2020), and disease (Wapinski and Chang 2011;Carlevaro-Fita et al 2020), the roles of TEs inside the lncRNAs has received less attention. One model suggests that TEs act as functional domains within lncRNAs, something akin to globular domains of proteins (Johnson and Guigo 2014;Chishima et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We and others recently showed that the majority of TERT transcripts are compartmentalized in the nucleus 39,40 , suggesting a potential regulatory mechanism acting at the level of RNA. TUG1 lncRNA has a role in many cellular processes and is associated with malignancies, where it has an oncogenic role (inferred as onco-lncRNA) [41][42][43][44][45][46][47][48][49] . We and others showed that TUG1 lncRNA is located in both the nucleus and cytoplasm and, correspondingly, it was shown to have a function in both compartments 31,50,51 .…”
Section: Introductionmentioning
confidence: 99%